2019
DOI: 10.3389/fmicb.2019.01104
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Alterations During HIV/SIV Infection: Implications for HIV Cure

Abstract: Gut mucosal damage, associated with Human Immunodeficiency Virus-1 (HIV) infection, is characterized by depletion in CD4 + T cells and persistent immune activation as a result of early epithelial barrier disruption and systemic translocation of microbial products. Unique approaches in studying both HIV infection in human patients and Simian Immunodeficiency Virus (SIV) infection in rhesus macaques have provided critical evidence for the pathogenesis and treatment of HIV/AIDS. While there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 94 publications
3
71
0
1
Order By: Relevance
“…[111][112][113] These lentiviral infections break down the integrity of the gastrointestinal mucosa and lead to alteration of gut microbiome and associated disease progression. [114][115][116] HIV-1/SIV infection induced the rapid loss of ILC3s in the intestinal mucosa. 117,118 Transcriptional profiling during acute infection revealed increased expression of genes linked with a strong IFN acute-phase response and evidence of gut barrier breakdown.…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…[111][112][113] These lentiviral infections break down the integrity of the gastrointestinal mucosa and lead to alteration of gut microbiome and associated disease progression. [114][115][116] HIV-1/SIV infection induced the rapid loss of ILC3s in the intestinal mucosa. 117,118 Transcriptional profiling during acute infection revealed increased expression of genes linked with a strong IFN acute-phase response and evidence of gut barrier breakdown.…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…One of the key physiological differences between primates that develop AIDS (humans, Macaca species) and SIV natural hosts, is that the latter maintains a healthy intestinal barrier despite the loss of mucosal CD4+ T cell subsets. We hypothesized that SIV-infected SMs would not exhibit the microbial dysbiosis reported in some studies for macaque species(29). At the phyla levels, the community structure between uninfected and SIV-infected SMs was largely similar and there was no significant differences between the levels of the predominant taxa Firmicutes (64% vs 61.5%, ns) or Bacteroidetes (28.7% vs 29.9, ns), nor differences in the next two most prevalent phyla, Spirochaetes (2.5% vs 3%) and Proteobacteria (2.1% vs 2.5%) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then assessed for global taxonomic genera differences and included a comparative analysis for each part of the study for Lactobacillus and Prevotella , as previous literature have reported these genera have a significant impact on mucosal immunity in SIV or HIV pathogenesis (29). The genus Lactobacillus has been correlated with the inhibition of IDO1 activity, and helping preserve mucosal TH17 CD4+ T cells and gastrointestinal mucosal integrity (30).…”
Section: Resultsmentioning
confidence: 99%
“…Clear changes in the gut microbiome composition have been reported between HIV-infected and uninfected individuals both in the early and chronic infection stage [37]. Although the fecal microbiota of healthy humans and macaques shares many similarities, there was not such strong clustering of bacterial communities associated with SIV infection as that in HIV infection [38].…”
Section: Comparison Of the Gut Microbiota And Metabonomic Pro Les Betmentioning
confidence: 95%